A survey of undergraduate anesthesia rotation in medical colleges of Pakistan - Fauzia Minai; M Irfan Ul Haq; Gauhar Afshan (Wolters Kluwer Medknow Publications, 2014)
Background: Student perceptions of specialties influence career choice decisions. It is important to expose undergraduates to the scope of rewarding careers in specialties like anesthesia by ensuring a good quality educational experience during anesthesia rotation. Our objective was to survey the curriculum structure and placement of the anesthesia undergraduate rotation in all the medical colleges of Pakistan recognized by the Pakistan Medical and Dental Council. Materials and Methods: A standardized survey questionnaire was distributed by direct contact, postal mail or e mail to one identified anesthetist in all recognized medical colleges with enrolment of 100 or more students. The response rate was 75%. We received responses by hand, email and postal mail. Results: We received responses from 15 out of 20 anesthetists contacted. 11 reported undergraduate anesthesia rotation while 4 reported absence of this rotation in their undergraduate curriculum. The rotation placement, duration and curriculum showed a wide variation and lack of standardization. Conclusion: Our survey indicates that the inclusion of anesthesia rotation in undergraduate medical education is not mandatory and standardized. The rotation duration, placement and curriculum need to be standardized to enhance the quality of the experience and promote the scope of the specialty for rewarding careers.